The use of Lopinavir and Ritonavir as a therapeutic alternative for COVID-19 - Silva, Eduarda Luiza Maciel da (2021)
Pandemy caused by the new coronavirus (SAR-CoV-2) represents a challenge for public health worldwide, due to the high transmissibility of the virus, consequent overload of health systems and large number of deaths. Studies and research are being carried out in order to identify safe and effective therapeutic alternatives for COVID-19, a disease caused by SAR-CoV-2, since there is still no consensus or scientific evidence that any drug can suppress viral excretion without causing massive side effects to the patient. In this perspective, some drugs are being used in clinical practice and, among them, is the combination of Lopinavir with Ritonavir, antiretroviral drugs commonly used in HIV treatment. The aim of this narrative review is to analyze the use of the Lopinavir/Ritonavir combination as a therapeutic alternative for COVID-19. The results indicate that the Lopinavir/Ritonavir combination has been used as an adjunctive treatment in cases of COVID-19, usually combined with other medications. Studies suggest that this combination does not interfere with ICU time and that the percentage of deaths is not significant. When applied at the onset of symptoms, these medications cause reduced viral excretion and fewer intubations. However, there is a contradiction regarding this, as some studies suggest an increase in viral excretion in patients who received these drugs. It reinforces the need to intensify studies related to treatment for COVID-19 in order to generate conclusive data so that medications can be used effectively and safely.